2015
DOI: 10.5851/kosfa.2015.35.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Combination of Smoking and Boiling on Quality of Korean Traditional Boiled Loin (M. longissimus dorsi)

Abstract: The combined effects of smoking and boiling on the proximate composition, technological quality traits, shear force, and sensory characteristics of the Korean traditional boiled loin were studied. Cooking loss, processing loss, and shear force were lower in the smoked/boiled samples than those in the control (without smoking treatment) (p<0.05). The results showed that the boiled loin samples between the control and treatment did not differ significantly in protein, fat, or ash contents, or pH values (p>0.05).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The range of pH after cooking was between 6.93 and 7.31, with beef sausage having the least pH value ( Table 4). This agrees with studies by Choi et al (2015), who reported that the pH of meat products increases with heating due to the imidazolium that is unfolded and exposed which has basic activity due to high histidine content. It is therefore advised to use vacuum packaging as already used for sausages due to their high susceptibility to spoilage and microbial attack with respect to their pH values being close to the neutral point.…”
Section: Sift Desksupporting
confidence: 93%
“…The range of pH after cooking was between 6.93 and 7.31, with beef sausage having the least pH value ( Table 4). This agrees with studies by Choi et al (2015), who reported that the pH of meat products increases with heating due to the imidazolium that is unfolded and exposed which has basic activity due to high histidine content. It is therefore advised to use vacuum packaging as already used for sausages due to their high susceptibility to spoilage and microbial attack with respect to their pH values being close to the neutral point.…”
Section: Sift Desksupporting
confidence: 93%
“…Similar reports in terms of overall acceptability were also reported by Choi et al . [39] in smoked meat products.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetics of matter losses during smoking and smoking‐drying processes was assessed. Thus, for each processing method, masses of three fresh fishes, which were randomly selected from different parts of a metal smoking tray and tagged, were tracked and recorded using an electronic balance (5 kg; Terraillon, Paris, France) every 30 min during the process and the yields were calculated at the end of the process 21,22 . Mass transfer associated with losses of water and fat during these processes was evaluated following Eqns (1) and (2) as proposed by Collignan and Raoult‐Wack 23 : WL=XtXt+1()mt+1mt FL=FtFt+1()mt+1mt Where WL is water loss between t and t + 1 (kg per 100 kg of product); FL is fat loss between t and t + 1 (kg per 100 kg of product); X t is water content at t (kg per 100 kg of product) (wet basis); X t + 1 is water content at t + 1 (kg per 100 kg of product) (wet basis); F t is fat content at t (kg per 100 kg of product) (wet basis); F t + 1 is fat content at t + 1 (kg per 100 kg of product) (wet basis); m t is mass of product at t (kg); and m t + 1 is mass of product at t + 1 (kg).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, for each processing method, masses of three fresh fishes, which were randomly selected from different parts of a metal smoking tray and tagged, were tracked and recorded using an electronic balance (5 kg; Terraillon, Paris, France) every 30 min during the process and the yields were calculated at the end of the process. 21,22 Mass transfer associated with losses of water and fat during these processes was evaluated following Eqns (1) and (2) as proposed by Collignan and Raoult-Wack 23 :…”
Section: Determination Of Thermal and Technological Characteristics O...mentioning
confidence: 99%
See 1 more Smart Citation